Progress in the study of aging marker criteria in human populations - He, Yan; Li, Zhe; Niu, Yue; Duan, Yuting; Wang, Qian; Liu, Xiaomin; Dong, Zheyi; Zheng, Ying; Chen, Yizhi; Wang, Yong; Zhao, Delong; Sun, Xuefeng; et al. (Frontiers in Public Health, 2024)
The use of human aging markers, which are physiological, biochemical and molecular indicators of structural or functional degeneration associated with aging, is the fundamental basis of individualized aging assessments. Identifying methods for selecting markers has become a primary and vital aspect of ageing research. However, there is no clear consensus or uniform principle on the criteria for screening aging markers. Therefore, we combine previous research from our center and summarize the criteria for screening aging markers in previous population studies, which are discussed in three aspects: functional perspective, operational implementation perspective and methodological perspective. Finally, an evaluation framework has been establ ished, and the criteria are categorized into three levels based on their importance, which can help assess the extent to which a candidate biomarker may be feasible, valid, and useful for a specific use context.